EVALUASI LAYANAN DI UPT PERPUSTAKAAN ITB (INSTITUT TEKNOLOGI BANDUNG) MENGGUNAKAN ANALISIS SWOT - Ayuningtyas, Vidya Wira (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
The title of this research is Evaluation of Services at UPT Library ITB (Bandung Institute of Technology) Using SWOT Analysis. The purpose of this research is to evaluate services at the ITB Library (Bandung Institute of Technology) using SWOT analysis. Libraries are information centres or information sources that have an important position in an organisation to support the success of the education process. Assessment of library service activities is all efforts, actions or processes to determine the quality of the progress of activities related to the implementation of library service programmes by referring to certain criteria or benchmarks in accordance with the programmes implemented. This research uses a qualitative descriptive approach. The approach used in this article is to reveal the evaluation of existing services at UPT Perpustakaan ITB by using SWOT analysis. strengths and opportunities, but can simultaneously minimise weaknesses, and threats.